Discovering Dysfunction in Title IX Implementation: NCAA Administrator Literacy, Responsibility, and Fear - Ellen Staurowsky; Erianne A. Weight (Journal of Applied Sports Management, 2013)
Higher education officials, including presidents and senior athletics administrators, are expected to voluntarily comply with the mandates of Title IX. In anticipation of the need for assistance in learning about the law’s requirements, Title IX regulations devised in the 1970s called for every institution in the country receiving federal financial assistance to appoint a Title IX coordinator to examine campus policies, practices, and philosophies in light of Title IX standards. As a result of the deficits in the application of this Title IX enforcement model, the purpose of this study was to assess how much senior athletics administrators know about basic Title IX information, how formally prepared they are to assume responsibility for Title IX compliance, how functional the Title IX enforcement mechanism is on their campuses, what insights they have to offer about the climate within athletics departments regarding Title IX compliance, and what they would change to achieve Title IX compliance with less stress and greater positive impact. Results reveal a moderate level of basic Title IX knowledge, moderate feelings of Title IX responsibility, and notable levels of fear and discomfort related to broaching equity issues. Knowledge and responsibility were fairly consistent across genders with a significant divide between male and female feelings of fear. The current lack of consistent and systematic education mechanisms may explain administrator decisions that are not in line with the law and tensions that frequently arise around gender equity issues within college and university athletics departments.
Keywords: Title IX; Title IX literacy; athletics administrators